Outcome of 5-Year Treatment of Neovascular Age-Related Macular Degeneration With Intravitreal Anti-VEGF Using “Treat and Extend” Regimen - Jaki Mekjavic, Polona; Zaletel Benda, Polona (Frontiers in Medicine, 2018)
Objective: The aim of this study is two-fold. First, to evaluate the long-term outcome of anti-vascular endothelial growth factor (anti-VEGF) treatment in a clinical setting using the »treat-and-extend regimen« (TER) in patients with neovascular age-related macular degeneration (nAMD). Second, to determine the proportion of patients treated with anti-VEGF with good visual acuity, i.e. vision sufficient to maintain a high level of independence. Design: We conducted a single center retrospective review of patients with treatment-naive nAMD that were treated with anti-VEGF. Patients were treated with anti-VEGF intravitreal injections according to the »treat-and-extend« (TER) regimen. Patients started treatment with monthly injections of either bevacizumab (1.25 mg/0.05 mL) or ranibizumab (0.5 mg/0.05 mL) until there were no signs present of choroidal neovascularisation (CNV) activity. CNV activity was determined from fundus examination and SD-OCT imaging. Follow-up administration of intravitreal injections was extended by 2-week intervals, up to a total of 14 weeks, provided no signs of CNV activity were detected. In some patients the first treatment was replaced with aflibercept (2 mg/0.05 ml). Participants: On the basis of the inclusion criterion for the study, that patients had to be treated for 5 years, a total of 101 patients were included in the study. In all patients, one eye was treated for a 5-year period, and thus we studied one hundred and one eyes. Measurements: Best corrected visual acuity (VA) was analysed at baseline, and each year during the five-year follow-up. Results: VA improved initially after year one of treatment. VA decreased in the subsequent four years of treatment, but remained significantly higher from year one to year three of the treatment compared to baseline values. Patients with good VA followed a similar trend: the proportion increased in the first year, and thereafter gradually decreased during the course of the 5-year follow up. At year 5 the number of patients with good VA decreased to baseline values. Conclusions: TER with anti-VEGF for nAMD treatment prevents long-term severe visual loss in real-world setting and maintains patients' VA at levels sufficient to ensure independence.